DEFROSTING THE CONFLICT IN TSKHINVALI: IS THE “REVOLUTION OF ROSES” STILL GOING ON? - SALDADZE, Malkhaz (CENTRAL ASIA AND THE CAUCASUS, 2004)
On 23 November 2003 we all witnessed un-expected political developments in Georgia, as a result of which the Shevardnadze regime, absolutely unable to cope with the crying social, economic, and political problems, was re-moved by a crowd driven to despair by a decade of stagnation. This challenge, which put an end to Eduard Shevardnadze’s long political career, is a Damocles Sword of sorts for the new Georgian cabinet and President Mikhail Saakashvili, whose charisma determined the outcome of the November events and kindled hopes for a better future. The new government received a huge credit of confidence which must be repaid.